Dynamic response of flexible square tunnels: centrifuge testing and validation of existing design methodologies - Tsinidis, Grigorios; Pitilakis, Kyriazis; Madabhushi, Gopol; Heron, Charles (Thomas Telford ICE Publishing, 2015)
A series of dynamic centrifuge tests were performed on a flexible aluminium square tunnel model embedded in Hostun dry sand. The tests were carried out at the centrifuge facility of the University of Cambridge in order to further improve knowledge regarding the seismic response of rectangular embedded structures and to calibrate currently available design methods. The soil–tunnel system response was recorded with an extensive instrumentation array, comprising miniature accelerometers, pressure cells and position sensors in addition to strain gauges, which recorded the tunnel lining internal forces. Tests were numerically analysed by means of full dynamic time history analysis of the coupled soil–tunnel system. Numerical predictions were compared to the experimental data to validate the effectiveness of the numerical modelling. The interpretation of both experimental and numerical results revealed, among other findings: (a) a rocking response of the model tunnel in addition to racking; (b) residual earth pressures on the tunnel side walls; and (c) residual internal forces after shaking, which are amplified with the tunnel's flexibility. Finally, the calibrated numerical models were used to validate the accuracy of simplified design methods used in engineering practice.